(untitled) (PRÁXIS EM SAÚDE, 2025)
The multicultural paradigm asserts the need for psychologists to recognize and incorporate their clients’ cultural dimension into the psychotherapeutic process. Studies have shown that culturally sensitive psychotherapy is a predictor of positive clinical outcomes. Nevertheless, in the Brazilian context, discussions on multiculturalism remain incipient compared to the international landscape. The aim of this study is to investigate the state of the art of the dialogue between multiculturalism and psychotherapy in Brazil. To this end, a critical review was conducted using the PePSIC, SciELO, and BVS databases, with the following keywords: “multiculturalism,” “multicultural psychology,” “multicultural competencies,” “multicultural orientation,” “cultural competence,” “cultural humility,” “psychotherapy,” “psychological care,” and “psychological intervention.” Five studies were selected based on inclusion criteria. The results indicated that, although the studies addressed cultural topics such as gender, race, religion/spirituality, and disability, they did not adopt the multicultural paradigm. These findings suggest limited consideration of intersectionality, little emphasis on the therapist’s cultural humility, and a restricted approach to the transversal development of cultural therapeutic skills.